2014
DOI: 10.1590/1806-9282.60.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders and associated factors among final-year healthcare students

Abstract: Common mental disorders and assoCiated faCtors among final-year healthCare students rev assoC med Bras 2014; 60 (6) Conflict of interest: noneObjective: to assess the prevalence of common mental disorder (CMD) and to identify potential associated factors among medical, dental and nursing students. Method: a cross-sectional study conducted in a public university in Northeast Brazil with 172 undergraduate students of the last three semesters of the medicine, dentistry and nursing courses, in February 2010, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 33 publications
2
26
2
21
Order By: Relevance
“…We included 59 studies in the qualitative analysis, and 57 [28][29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51][52] studies involving a total of 18,015 medical students in the quantitative analysis (Table 1). All forest plots are available on request from the authors.…”
Section: Resultsmentioning
confidence: 99%
“…We included 59 studies in the qualitative analysis, and 57 [28][29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51][52] studies involving a total of 18,015 medical students in the quantitative analysis (Table 1). All forest plots are available on request from the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Undertaking integrated evidence-based intervention focusing on students with poor sleep quality, poor physical health, and who drank alcohol is essential if the present finding confirmed by a longitudinal study. The high prevalence of CMD suggests that immediate preventive and curative measures should be implemented, such as the setting up of psycho-pedagogic support and counseling services to build students resilience [53]. Life skill training is also required to openly discuss and actively address the problems during university education [55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of CMD among Dutch university medical students was 48–54% [52]. Another cross-sectional study conducted at the public university in Northeast Brazil reported that the prevalence of CMD was 33.7%; the risk factors were gender, lack of good expectations regarding the future, course as not a source of pleasure, and feeling emotionally tense [53]. …”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, as prevalências combinadas de depressão, ansiedade, transtornos mentais comuns e uso problemático de álcool entre estudantes de medicina no Brasil variaram de 30,6% a 32,9% (Pacheco et al, 2017). Em um estudo desenvolvido por Costa et al (2014) utilizando o BDI com internos de medicina em uma universidade pública, a prevalência geral de depressão foi de 40,5%. Um estudo da Universidade de Pernambuco (UPE) entre estudantes de alguns cursos de saúde encontrou uma prevalência geral de depressão de 34,1%.…”
Section: Introductionunclassified